Influence of hydrogen and helium plasma streams exposures on modification of tungsten structure under powerful transient loads - Makhlaj, V.A.; Garkusha, I.E.; Byrka, O.V.; Chrebotarev, V.V.; Landman, I.S.; Lebedev, S.I.; Malykhin, S.V.; Pugachev, A.T.; Shevchuk, P.B.; Tereshin, V.I. (Вопросы атомной науки и техники, 2011)
Influence of plasma exposures on tungsten behavior was studied in QSPA Kh-50 facility and pulsed plasma gun PPA. Plasma loads were chosen either below the melting threshold or resulting in pronounced melting. Evolution of residual stresses and lattice spacing was studied for various number of hydrogen or helium plasma impacts. The value of residual stresses depends on irradiation dose and kind of impact plasma. The non monotone change of lattice spacing was observed for melted surface. The damage of exposed surface was caused by cracks appearing.